Highlighting the factors of energy intensity change in Malaysia: Input-output approach - Bekhet H.A.; Abdullah A. (Regional Energy Resources Information Center (RERIC), 2023)
Energy utilization; Public policy; Contributing factor; Energy intensity; Input output model; Input-output approach; Malaysia; Policy implications; Production structures; Structural decomposition analysis; Energy efficiency